International school leadership in malaysia: Exploring teachers’ perspectives on leading in a culturally diverse environment - Velarde, Joseph M.; Ghani, Muhammad Faizal A. (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2019)
International schools present a promising setting in the exploration of leadership in culturally diverse organisations. Due to heightened global interconnectivity, the increasing number of international schools in the Asia Pacific region leads to the ever-growing formation of multicultural learning environments. Aside from being one of the countries with the largest number of international school students in Southeast Asia, Malaysia offers a socio-culturally distinct venue for understanding the organisational dynamics of international schools in a heterogeneous society. Hence, this study primarily aims to present the perspectives of international school teachers on the practices and programmes employed by school leaders with respect to cultural diversity. Taking the viewpoints of school teachers, this case study focuses on how school leaders perform in the midst of the culturally diverse environment of an international school in Malaysia. Thirteen teachers from a prominent international school in Kuala Lumpur were purposefully selected to participate in semi-structured interview sessions. To substantiate the responses from the interviews, five teachers from the same school participated in a focus group discussion. The data from the individual interviews and focus group discussion were triangulated with observation field notes and document analysis. The collated data were thematically analysed using Atlas.ti. The emerging themes revolve around the following: leadership practices with respect to cultural diversity; programmes and policies promoting cultural awareness; and, leadership effects on the school community. Having students and teachers coming from different socio-cultural backgrounds, international schools pose both opportunities and challenges for leadership. Guided by the findings of this study, international school leaders and teachers may design their curriculum and initiate new co-curricular or organisational programmes promoting cultural diversity to benefit students and teachers. More than identifying leadership practices and institutionalised programmes in managing cultural differences, this study calls for further introspection and action to harness the potentials of leadership in promoting harmony in diversity for societal development. © 2019, University of Malaya. All rights reserved.